Detwinning through migration of twin boundaries in nanotwinned Cu films under in situ ion irradiation. Issue 1 (31st December 2018) - Du, Jinlong; Wu, Zaoming; Fu, Engang; Liang, Yanxiang; Wang, Xingjun; Wang, Peipei; Yu, Kaiyuan; Ding, Xiangdong; Li, Meimei; Kirk, Marquis
Abstract: The mechanism of radiation-induced detwinning is different from that of deformation detwinning as the former is dominated by supersaturated radiation-induced defects while the latter is usually triggered by global stress. In situ Kr ion irradiation was performed to study the detwinning mechanism of nanotwinned Cu films with various twin thicknesses. Two types of incoherent twin boundaries (ITBs), so-called fixed ITBs and free ITBs, are characterized based on their structural features, and the difference in their migration behavior is investigated. It is observed that detwinning during radiation is attributed to the frequent migration of free ITBs, while the migration of fixed ITBs is absent. Statistics shows that the migration distance of free ITBs is thickness and dose dependent. Potential migration mechanisms are discussed. Abstract :